Osteopoikilosis - Hasan, SA; Siddiq, AB; Moula, A; Khasru, MR; Kaiser, MS; Salek, AK (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):290-3. The abstract of this article is available on the PubMed website